Palliative Care for Cancer Patients and their Relatives in Dutch Community-Based Psychosocial Support Centers (CBPSCs) - Visser, Adriaan (Journal of Palliative Care And Hospice, 2021)
Aim Community-based psychosocial support centers for cancer patients and their relatives (CBPSCs), developed in the Netherlands, offer easily accessible contacts with fellow patients and support by trained volunteers. We studied the characteristics of visitors of CBPSCs, which palliative support they need and receive, and how satisfied they are with this support. Methods The role of 20 CBPSCs was explored in semi-structured interviews among 34 visitors with regard to their contacts with CBPSCs on palliative care (study 1). Additionally, in 25 CBPSCs, 701 visitors filled out a web-based questionnaire about their experiences with the palliative care (study 2). Within this second study, 25 coordinators of CBPSCs also answered questions about the palliative care (study 3). Results The cancer patients and proxies stressed the view that palliative support should be a part of the support by CBPSCs. This belief was confirmed by the coordinators. Not only attention to the reduction of symptoms, but also emotional support and information supply should be offered when recovery is no longer possible. Talking about death and dying may be worrying for some visitors in a better condition. Education of the volunteers is needed, taking into account the conditions in the CBPSCs e.g., the already existing experience with the palliative care in the CBPSCs and participation in regional networks. Practical Implications Further development of the attention given to palliative support, training and research in that field is needed.
Keywords: CBPSCs; palliative support; palliative care networks; people with cancer